Perception of effort, enjoyment and learning in secondary students in physical education lessons during a Crossfit teaching unit - Sánchez-Alcaraz Martínez B. J.; Gómez-Mármol A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2015)
This research aims to know the enjoyment, learning and intensity level perception in Physical Education lessons during a CrossFit Educational Component and the relationship among gender and educational level. In order to that, a total of 104 secondary students whose ages vary from 12 to 16 years old have filled in two questionnaires about enjoyment, learning and effort perception. The results have shown high levels of enjoyment, effort and learning perception in the students thought CrossFit practice. Thus, boys perceive higher enjoyment and intensity than girls, and it has found that students in upper secondary perceive physical education lessons as more intense and less fun.